2015
DOI: 10.2503/hortj.mi-050
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Gibberellins in the Regulation of Tillering in Welsh Onion (<i>Allium fistulosum</i> L.)

Abstract: We investigated the effects of applied gibberellin A 3 (GA 3 ) and uniconazole P (UCP), a GA biosynthesis inhibitor, on tillering in Welsh onion, also known as Japanese bunching onion 'Hangzhou', a cultivar with very high tillering capacity. The number of tillers was increased by GA 3 treatment and reduced by UCP treatment. The tillering-inhibitory effect of UCP was counteracted by GA 3 treatment. GAs were considered to be involved in not axillary bud outgrowth but its initiation for the following results: UCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The semi‐dwarf switchgrass lines showed an increase in tiller number, whereas dwarf lines displayed a reduction in number of tillers per plant relative to wild‐type controls (Wuddineh et al ., ). On the other hand, GAs were shown to increase tiller numbers of Welsh onion by initiating and promoting axillary bud development (Yamazaki et al ., ). In addition, Ni et al .…”
Section: Discussionmentioning
confidence: 97%
“…The semi‐dwarf switchgrass lines showed an increase in tiller number, whereas dwarf lines displayed a reduction in number of tillers per plant relative to wild‐type controls (Wuddineh et al ., ). On the other hand, GAs were shown to increase tiller numbers of Welsh onion by initiating and promoting axillary bud development (Yamazaki et al ., ). In addition, Ni et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies suggested GAs play a negative role in the regulation of shoot branching in various species [ 44 , 45 , 46 ]. Recently, stimulation of GAs in axillary bud development was reported in cherry tree [ 17 ], Jatropha curcas [ 18 ] and Welsh onion [ 19 ]. Our previous study showed injection of GA 3 four times (at 40, 50, 60 and 70 days after planting) promoted axillary bud formation and increased clove number per bulb (control and GA 3 treatment: 12 and 24, respectively) in cv.…”
Section: Discussionmentioning
confidence: 99%
“…The clove includes a bud, a storage leaf and a protective leaf, which is equated with tiller in rice and branch in woody plants [ 13 ]. Furthermore, gibberellins (GAs), as indispensable stimulators of plant growth [ 15 ], are applied to induce lateral bud outgrowth in tomato [ 16 ], branches in cherry trees [ 17 ] and Jatropha curcas [ 18 ], and tiller in Welsh Onion [ 19 ]. Our previous study showed injection of GA 3 promoted axillary meristem formation and increased clove number per bulb [ 20 ], which is a better tool to enhance propagation efficiency and bulb yield of garlic [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In potatoes, it was testified that GA 3 treatment improved the number of tubers per plant [68]. The application of GA 3 also encouraged tillering in welsh onions [69], encouraged airborne tubers development in turnip [70], and promoted shoot branching in Jatropha curcas [71]. GA was also used to progress fruit morphological characteristics (skin color and firmness) and nutritive quality in apples, bananas, plums, and sweet peppers [72][73][74] ( Table 1).…”
Section: Gibberellic Acidmentioning
confidence: 99%
“…Exogenous GA 3 induced the axillary bud formation of garlic via the changes of soluble sugar content and soluble protein content in the stem [88]. Exogenous gibberellic acid (GA 3 ) induced axillary bud formation and promoted the growth of lateral branches in tomato [89], potato [90], cherry tree [91], Jatropha curcas [71], and welsh onion [69]. The application of exogenous GA 3 not only intensely increased clove number per bulb but also changed bulb morphology [75].…”
Section: Gibberellic Acidmentioning
confidence: 99%